Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

Age-dependent effects of social isolation on mesolimbic dopamine release - Megan A. McWain; Rachel L. Pace; Patricia A. Nalan; Deranda B. Lester (Experimental Brain Research, 2022)

Cerebellar Modulation of Mesolimbic Dopamine Transmission Is Functionally Asymmetrical - Zade R. Holloway; Nick B. Paige; Josiah F. Comstock; Hunter G. Nolen; Helen J. Sable; Deranda B. Lester (The Cerebellum, 2019)

Genotype-dependent effects of adolescent nicotine exposure on dopamine functional dynamics in the nucleus accumbens shell in male and female mice: a potential mechanism underlying the gateway effect of nicotine - Price E. Dickson; Tiffany D. Rogers; Deranda B. Lester; Mellessa M. Miller; Shannon G. Matta; Elissa J. Chesler; Dan Goldowitz; Charles D. Blaha; Guy Mittleman (Psychopharmacology, 2011)

Increased amphetamine-induced locomotor activity, sensitization, and accumbal dopamine release in M5 muscarinic receptor knockout mice - Lene S. Schmidt; Anthony D. Miller; Deranda B. Lester; Cecilie Bay-Richter; Christina Schülein; Henriette Frikke-Schmidt; Jürgen Wess; Charles D. Blaha; David P. D. Woldbye; Anders Fink-Jensen; Gitta Wortwein (Psychopharmacology, 2010)